Internalisasi Nilai-Nilai Toleransi dalam Pembelajaran Pendidikan Agama Islam di SMA Negeri 1 Lhokseumawe - Muhammad Usman; Anton Widyanto (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2019)
Diversity in Indonesia is part of the nation and should be embraced by its people. Managing diversity requires high tolerance. School is the best place to prepare the next generation for internalizing the values of tolerance and for respecting peace in the future. However, these values need all components of the society to properly achieve. When a school has pluralist conditions, it is important to pay attention to the students’ trust in order to successfully internalize tolerance values. Therefore, heterogenity will not produce the anti-tolerant generation. The study took place in SMA Negeri (public senior high school) 1 Lhokseumawe. The school was quite diverse and heterogenous where there were Muslim and non-Muslim students. The purposes of the study were to find out the tolerance values within Islamic education learning, to understand the internalization process, and to map the supporting and hindering factors of the internalization process of the tolerance values in SMAN 1 Lhokseumawe. This was a qualitative approach. Data were collected by interview, observation, and documentation of the school. This study resulted in some findings. Firstly, the values of tolerance received by the students included appreciation, brotherhood, freedom, cooperation, helping one another, non discrimination, and sharing. Secondly, the internalization process of the values was done in three ways: integration, the school customs, and extracurricular activities. Thirdly, the factors supporting the internalization were qualified and competent teacher, active student extracurricular activities, fair access of facilities, cooperation among teachers, support from school principal, heterogeneous awareness, active alumni, increased interest and state policy. Meanwhile, the factors hindering the internalization involved the unavailability of tolerance-based module, the unavailability of tolerance-based coaching, increased racism, religion, and other sensitive issues, and massive intolerant news from the media. It is recommended that learning module and teacher training should be tolerance specified in order to enforce the process of internalizing the tolerance values in school and reduce the intolerant issues widely spread in the mass media.